AR Interfaces for Disocclusion-A Comparative Study - Liao, Shuqi; Zhou, Yuqi; Popescu, Voicu (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2023)
An important application of augmented reality (AR) is the design of interfaces that reveal parts of the real world to which the user does not have line of sight. The design space for such interfaces is vast, with many options for integrating the visualization of the occluded parts of the scene into the user's main view. This paper compares four AR interfaces for disocclusion: X-ray, Cutaway, Picture-in-picture, and Multiperspective. The interfaces are compared in a within-subjects study (N = 33) over four tasks: counting dynamic spheres, pointing to the direction of an occluded person, finding the closest object to a given object, and finding pairs of matching numbers. The results show that Cutaway leads to poor performance in tasks where the user needs to see both the occluder and the occludee; that Picture-in-picture and Multiperspective have a visualization comprehensiveness advantage over Cutaway and X-ray, but a disadvantage in terms of directional guidance; that X-ray has a task completion time disadvantage due to the visualization complexity; and that participants gave Cutaway and Picture-in-picture high, and Multiperspective and X-ray low usability scores.